Cyber Security Awareness, Knowledge and Behavior of Digital Banking Users in Salatiga - Nagari, Salma Faundria; Raharja, Surya (Asia Pacific Fraud Journal, 2025)
Digital banking has become one of the fastest-growing techno-logical advances in the banking sector. This study aims to analyze the relationship between cybersecurity awareness, knowledge, and behavior among digital banking users in Salatiga City. Using a quantitative approach, data were collected from 200 respondents and analyzed with SmartPLS 4. The results show that cybersecurity knowledge has a significant positive influence on both awareness and behavior. Awareness also directly affects behavior. However, awareness does not significantly mediate the relationship between knowledge and behavior. This implies that while awareness is important, knowledge plays a more dominant role in shaping users’ cybersecurity behavior. This study contributes to the banking industry by providing insights to enhance user cybersecurity through targeted education and awareness programs. Additionally, it enriches the academic literature on cybersecurity behavior in the context of digital banking users, particularly in developing regions. Future research is encouraged to explore other influencing factors such as motivation, perceived risk, or institutional support.